The Effect of Price, Product and Place on The Purchase Decision of Kopi Janji Jiwa Samarinda in Islamic Economic Perspective - Vira Paradina Winata; Darmawati Darmawati; Irma Yuliani (At-Taradhi Jurnal Studi Ekonomi, 2023)
This study aims to determine the effect of price, product and place on purchasing decisions for Kopi Jiwa Samarinda in the perspective of Islamic economics. This type of research is quantitative research. The method used is descriptive associative. The sampling technique is non-probability sampling with (accidental sampling). The types of data in this study are primary and secondary. The sampling method used is using the Cochran formula with a sample of 96 respondents and rounded up to 100 respondents. Methods in collecting data in this study using observation, questionnaires (questionnaires), and documentation. The data analysis technique in this study uses validity test, reliability test, classical assumption test consisting of (normality test, multicollinearity test, heteroscedasticity test, autocorrelation test and linearity test), and multiple linear regression analysis test (t test, f test, and the coefficient of determination test (R2).The results of this study indicate that the price variable has no significant effect on the Purchase Decision of Promise Jiwa Samarinda Coffee with a sig value of 0.095 > 0.05, the product variable has a significant effect on the Purchase Decision of Kopi Jiwa Samarinda with a sig value of 0.000 < 0.05, and the place variable does not have a significant effect on the purchasing decision of the Promised Jiwa Samarinda Coffee in the Islamic Economic Perspective with a sig value of 0.271 > 0.05. Meanwhile, the price, product, and place variables simultaneously have a significant effect on the purchasing decision of Promise Coffee. The soul of Samarinda in the perspective of Islamic Economics with a sig value as follows: esar 0.000 < 0.05. This shows that 49.0% of the Purchase Decision variables are influenced by Price (X1), Product (X2), and Place (X3). And the rest (100% - 49.0%) = 51.0% is influenced by other variables not discussed in this study. So the influence contribution of all variables in this study is 51.0%.